Epidemiology of Pediatric Traumatic Brain Injury at Sylvanus Olympio University Hospital of Lomé in Togo - Pilakimwe Egbohou; Tabana Mouzou; Pikabalo Tchetike; Hamza Doles Sama; Sarakawabalo Assenouwe; Gnimdou Akala-Yoba; Lonlongnon Randolph; Kadjika Tomta (Anesthesiology Research and Practice)
Introduction. Severe pediatric traumatic brain injury (pTBI) is a leading cause of disability and death in children worldwide. Children victims of pTBI are admitted to the Sylvanus Olympio University Hospital (SOUH) at the multipurpose Intensive Care Unit (ICU). We aimed in this study to describe the epidemiologic characteristics and outcomes of pTBI patients admitted in this ICU. Patients and Methods. This study was conducted at the ICU of SOUH of Lome. It was a retrospective study based on patients’ records from 0 to 15 years old admitted during the period from 1 January 2012 to 30 June 2018 (5 years and 6 months). Results. We recorded 91 pTBI included in the study. The mean age was 7.7 ± 4.3 years. The male predominated with 67.0%. Road traffic accidents were the most common cause (79.1%), followed by falls (19.8%). The average pediatric Glasgow Coma Scale (pGCS) was 6.6 ± 1.4, with a mean Injury Severity Score (ISS) of 23.1 ± 8.4. The most common brain injuries found in the CT scan were brain edema (72.9%), skull fracture (69.5%), and brain contusion (55.9%). The average duration under mechanical ventilation was 2.1 ± 2.9 days, and the mean ICU stay was 4.9 ± 4.4 days. Overall mortality was 31.9% (29 cases). Factors significantly associated (p<0.05) with death were hypotension (51.7%), anemia (43.1%), hyperthermia (46.7%), GCS < 6 (64%), and ISS > 20 (48.9%). Conclusion. pTBI mortality remains high in SOUH ICU. Factors associated with mortality were secondary systemic insults, worse GCS < 6, and ISS > 20.